Alejo Carpentier: las luces del siglo - San José, Eduardo (Anales de Literatura Hispanoamericana, 2008)
Alejo Carpentier’s El siglo de las luces [Explosion in a Cathedral] approaches the Eighteenth Century historically and ideologically to discuss issues such as historical progress, utopia and revolution. Literary critics have debated for decades Carpentier’s proposal. Their conclusions can either be divided into those reading the novel as sceptical towards the idea of progress, and those supporting its affiliation with the univocal progress model characteristic of the Enlightened Modernity. These conclusions are generally based on the study of the novel’s narrative structure. This article analyses this matter through a study of the novel’s symbolical level, where the topic of light is organised in allegories expressing Carpentier’s theoretical position on these concepts.